Context-dependent preferences vary by multicomponent signals in a swordtail. (July 2017) - Reding, Luke; Cummings, Molly E.
Abstract : Female mating preferences can be both context dependent and based on the assessment of multicomponent male signals. Here, we assess the social context dependence of female mating preferences for two components of a male's multicomponent signal. We dissected the visual signal of male Xiphophorus nigrensis swordtails, a species in which males vary by both size and degree of courtship, to test (1) how the identity of males in a given choice influences female mating preferences and (2) how females perceptually integrate a male's multicomponent signal. We used validated male animations that generate repeatable female responses to test mating preferences for size and courtship vigour, separately and together, using dichotomous choice tests. When keeping courtship vigour constant, females discriminated between males only when there was a large size difference between them. When keeping size constant, the identity of males in a choice reversed a preference for a vigorously courting male. We found no evidence that females perceptually bind the separate components of a male's signal additively. However, females were faster to approach males when the males varied in both size and courtship than when the males only varied in size, perhaps favouring the evolution of multicomponent signals in males. Highlights: Females often base mating decisions on assessment of multicomponent male signals. We tested female preferences for male animations that varied in size and courtship. Large males were preferred only when they were paired with a small male. Females approached males faster when they varied in both size and courtship.